Nutrition in the prevention and treatment of endometriosis: A review - Barnard, Neal D.; Holtz, Danielle N.; Schmidt, Natalie; Kolipaka, Sinjana; Hata, Ellen; Sutton, Macy; Znayenko-Miller, Tatiana; Hazen, Nicholas D.; Cobb, Christie; Kahleova, Hana (Frontiers in Nutrition, 2023)
Endometriosis is characterized by the presence of endometrial tissues outside the uterine lining, typically on the external surface of the uterus, the ovaries, fallopian tubes, abdominal wall, or intestines. The prevalence of endometriosis in North America, Australia, and Europe is approximately 1–5% in women of reproductive age. Treatment options for endometriosis are limited. While over-the-counter medications may be used to reduce acute pain, hormonal treatments are common and may result in subfertility. In more severe cases, laparoscopic excision procedures and even hysterectomies may be performed to negate the painful effects of endometriosis. Nutritional interventions may be helpful in the prevention and treatment of endometriosis. Reducing dietary fat, specifically animal fats, and increasing dietary fiber has been shown to reduce circulating estrogen concentrations and may be beneficial for individuals with endometriosis. Meat consumption is associated with greater risk of developing endometriosis. Anti-inflammatory properties of plant-based diets may benefit women with endometriosis. Additionally, seaweed holds estrogen modulating properties that have benefitted postmenopausal women and offers potential to reduce estradiol concentrations in pre-menopausal women. Furthermore, consumption of vitamin D has been shown to reduce endometrial pain via increased antioxidant capacity and supplementation with vitamins C and E significantly reduced endometriosis symptoms, compared with placebo. More randomized clinical trials are needed to elucidate the role of diet in endometriosis.